Four individually identified paired dopamine neurons signal taste punishment in larval Drosophila - Denise Weber; Katrin Vogt; Anton Miroschnikow; Michael J Pankratz; Andreas S Thum (eLife)
Dopaminergic neurons (DANs) play key roles in processing rewards and punishments across species. They evaluate sensory input, store memories, and update them based on relevance. To understand how individual DANs contribute to these functions, we studied Drosophila larvae, which have only about 120 DANs. Only eight of these project to the mushroom body (MB), a center for olfactory learning. These eight are divided into the pPAM and DL1 clusters, with four DANs each. We confirmed that pPAM neurons in the MB medial lobe encode sugar rewards. In the DL1 cluster, four neurons—DAN-c1, DAN-d1, DAN-f1, and DAN-g1—each target different MB regions. Notably, optogenetic activation of DAN-f1 and DAN-g1 can substitute for punishment. Additional methods (inhibition, calcium imaging, connectomics) show each DL1 DAN encodes a unique aspect of punishment, with DAN-g1 being pivotal for salt-based signals. Our findings reveal a clear division of labor among larval DL1 DANs for encoding punishment. The striking resemblance in the organizing principle of larval DANs with that of its adult counterpart and the mammalian basal ganglion suggests that there may be a limited number of efficient neural circuit solutions available to address more complex cognitive challenges in nature.